Digitalization and Carbon Footprint: Does ICT Reduce Carbon Footprint? - Mohamed, Manar; Helmy, Omneia; Ibrahiem, Dalia M. (Digital Technologies Research and Applications, 2025)
The potential economic and social benefits of digitalization are far-reaching and frequently discussed in public discourse. It is often portrayed as a silver bullet for addressing the world’s increasingly urgent environmental challenges. In particular, digitalization is considered a key enabler of a low-carbon economy. However, realizing these technological potentials requires effective implementation in sectors with the greatest capacity for smart solutions—namely, transportation, buildings, and energy—to reduce the carbon footprint. Conversely, digital technologies can also contribute to an increased carbon footprint due to the complexities involved in constructing and maintaining digital infrastructures, as well as rebound effects. Therefore, the impact of digitalization on the carbon footprint is a subject of particular interest. This paper examines the effect of digitalization on the carbon footprint in the MENA region during the period from 2000 to 2022. The Generalized Method of Moments (GMM), Fully Modified Ordinary Least Squares (FMOLS) and the Dumitrsc-Hurlin causality test are employed for this analysis. The GMM results indicate that information and communication technology (ICT) has no significant impact on the carbon footprint in the short run. In contrast, the FMOLS results show that ICT is negatively associated with the carbon footprint in the long run. The causality test indicates robust evidence of unidirectional causality running from ICT to Carbon footprint in the MENA region, asserting the long-run estimation results.